Identifikasi Praktik dan Hambatan Guru dalam Asesmen Kognitif Matematika di Masa Pandemi COVID-19 - Hajra Yansa; Heri Retnawati (Jurnal Elemen, 2021)
This study aims to identify teachers' practices and barriers in carrying out a cognitive mathematics assessment during the COVID-19 pandemic. The type of research used is an online survey using a google form, which is spread over ten days via WhatsApp. This survey uses a qualitative approach. The research instrument was constructed from a pocketbook of periodic diagnostic assessment. A total of 78 primary to secondary school teachers from various regions in Indonesia participated. Data analysis was done descriptively, while data from open questions were analyzed using Atlasti 9. The study results present the practice of cognitive assessment regularly carried out by online-based mathematics teachers in high-grade elementary schools to secondary schools. In contrast, low-grade elementary schools are conducted by home visit. In practice, teachers experience several obstacles: the validity of the answers, limited time in the assessment, barriers from students themselves, and facilities. These obstacles cause the assessment results not to describe the cognitive level in-depth or provide valid and reliable information regarding students' achievement.